PENGARUH GAYA KEPEMIMPINAN, KERJASAMA TIM, DAN BUDAYA ORGANISASI TERHADAP PRESTASI KERJA DAN DAMPAKNYA KEPADA KINERJA PEGAWAI - Imron Imron; suhardi suhardi (LPPM STIE PERTIBA Pangkalpinang, 2019)
This study aims to examine the leadership style, teamwork, organizational culture on work performance and its impact on employee performance in the Culture and Tourism Office of the Bangka Belitung Islands Province. The method in this study uses survey methods and questionnaires to all respondents totaling 58 respondents. This study uses quantitative analysis of primary data from field surveys. The results of the study concluded that there was a variable influence of leadership style, teamwork and organizational culture on employee work performance. Future research is expected to add other independent variables and add dimensions of each variable in order to increase deeper knowledge. The results of this study can be used as a reference for researchers who will investigate further. And it is also expected to carry out assessments in a deeper and broader scope.